Compressive optical spectrometry based on sequency-ordered Hadamard transform - Zhang, Yi (2021)
We propose a compressive Hadamard transform spectrometer (CHTS) based on the energy compaction trait of the sequency-ordered Hadamard matrix (SOHM), in which the spectrum is reconstructed from compressed measurements using simple matrix multiplication. The evaluation of a 128-channel CHTS on the measurements of a fluorescence spectrum demonstrates compression ratios up to 8:1, with a relative root mean square error of around 3%.